DINAMIKA PERILAKU KONSUMEN MINUMAN KOPI DI MASA PANDEMI PADA KALANGAN MAHASISWA (Suatu Kasus Pada Mahasiswa Angkatan 2018 Program Studi Agribisnis Fakultas Pertanian Universitas Padjadjaran) - Briani Fahriah Ramadhani Purnomo; Dini Rochdiani; Elly Rasmikayati; Dhany Esperanza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Drinking coffee has now become a lifestyle among college students. There are various types of coffee drink products that can be consumed, such as coffee shop-processed drinks and instant coffee. Since December 2019, there has been an outbreak of the Covid 19 disease and the issuance of a Large-Scale Social Restriction, leading to changes in consumer behavior in buying coffee drink products. The purpose of this study was to find out how the consumer behavior of coffee drink products before and during the pandemic among college students, and whether there were changes in consumer behavior of coffee drink products before and during the pandemic among college students. This research uses descriptive analysis with a survey method. The study was conducted on students of the Agribusiness Major, Faculty of Agriculture, Universitas Padjadjaran, with a sample of 100 people. The data analysis technique used is descriptive analysis. The results showed: (1) Prior to the pandemic, the majority of students received information from social media, received funds from their parents, consumed coffee shop-processed drinks, consumed it at the coffee shops, made purchases using the offline method, paid by cash, consuming it at a coffee shop at night, evaluating the product, and evaluate the product directly (2) During the pandemic period, the majority of students get information sources from social media, get funds from their parents, consume coffee shop-processed drinks, consume it at the coffee shops, make purchases using the offline method, make payments using e-wallet, consuming it at home in the afternoon, and not evaluating the product. (3) There are changes in some consumer behavior of coffee drink products among students.